Small-Scale Natural Wastewater Treatment Systems: Principles and Regulatory Framework - Kiara Winans; Shanin Speas-Frost; Mike Jerauld; Mark Clark; Gurpal Toor (EDIS)
Natural systems use the natural processes of wetland ecosystems to both transform and hold on to many of the common pollutants that occur in household wastewater. This 8-page fact sheet briefly describes the principles and added benefits of natural systems. It then focuses on their use for treating small municipal wastewater flows from commercial and residential sites (i.e., septic systems or decentralized wastewater systems). Written by Kiara Winans, Shanin Speas-Frost, Mike Jerauld, Mark Clark, and Gurpal Toor, and published by the UF Department of Soil and Water Science, May 2012.